Laryngotracheal reconstruction with a prefabricated fasciocutaneous free flap for recurrent papillary thyroid carcinoma. Issue 11 (4th July 2016) - Cheng, Olivia T.; Tamaki, Akina; Rezaee, Rod P.; Zender, Chad A.
ABSTRACT: Background: Prefabricated composite free flaps have been described as a technique for reconstruction of laryngotracheal defects. Methods: We present a 74‐year‐old woman with recurrent papillary thyroid carcinoma (PTC) who was initially treated with thyroidectomy, tracheal resection, and subsequent vocal cord medialization. The patient's recurrent disease was treated with partial laryngectomy and reconstruction using a prefabricated composite free flap. A 2‐stage procedure was performed using conchal cartilage to create a prefabricated radial forearm free flap. Results: The patient's airway was successfully reconstructed with preservation of speech and swallow function. Conclusion: This case provides further evidence supporting the use of prefabricated free flaps in airway reconstruction and the ability to obtain successful outcomes in a patient with multiple prior surgeries in the operative field and requiring adjuvant external beam radiation therapy. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2512–E2514, 2016